THE EFFECTS OF FOUR PESTICIDES ON THE GROWTH OF CHLORELLA VULGARIS - Agirman, Nur; Kendirlioglu, Gokce; Cetin, A. Kadri (Parlar Scientific Publications (P S P), 2014)
w In this study, the effects of pesticides (diazinon, dichlorvos, trifluralin, paraquat) on the growth of Chlorella vulgaris were examined. In laboratory studies, it was observed that growth of Chlorella vulgaris (microalgae) decreased with increasing concentrations of the above pesticides and exposure time for 1-6 days whereas in all corresponding control cultures, the growth rate of Chlorella vulgaris was always positive. Results demonstrated that C. vulgaris microalgae had different sensitivities towards dichlorvos, diazinon, trifluralin and paraquat but their effects on growth were quite similar. These results demonstrated adverse effects of dichlorvos, diazinon, trifluralin and paraquat upon freshwater algae; thus, the application of these pesticides in agricultural practices must be done carefully, since any disturbance affecting algae with similar or higher sensitivity will have severe repercussions on higher trophic levels.
Keywords: Chlorella vulgaris; algal sensitivity; diazinon; dichlorvos; trifluralin; paraquat